(untitled) (Research, Society and Development, 2023)
The present research deals with the family agroindustry as one of the pillars that propitiate the strengthening of in the main streets of the cities of Brazil it is common to find the so-called flannels. The objective of these people is to carry out an activity that provides income and guarantees the support of the family. Brazil has always faced challenges in designing, implementing and implementing public policies. These difficulties mainly affect the low-income population who live on the margins of society. The objective of this research was to analyze municipal public policies that serve informal traffic light workers in the city of Patos -PB. Therefore, a descriptive quantitative research was carried out in order to allow a better understanding of the problem. In addition, the research also used a literary collection composed of articles, books, dissertations and theses, as well as data obtained through websites of official institutions that demonstrate direct and indirect correlations with the study proposal. A field survey was also carried out between February and March 2023, with about 10 flannels. As a result, it can be observed that the existing public policies in the city of Patos - PB are directed to all low-income citizens, not specifically to the flannels. In relation to child labor, it was found that despite the inspections, the problem still persists, due to the lack of consistency in the daily inspection. As a suggestion, the present study exposed the need for constant inspections in relation to child labor of the flannels and the elaboration and implementation of public policies aimed at these people in a special way.